Protein microarray with horseradish peroxidase chemiluminescence for quantification of serum α-fetoprotein. (October 2015) - Zhao, Yuanshun; Zhang, Yonghong; Lin, Dongdong; Li, Kang; Yin, Chengzeng; Liu, Xiuhong; Jin, Boxun; Sun, Libo; Liu, Jinhua; Zhang, Aiying; Li, Ning
Objectives: To develop and evaluate a protein microarray assay with horseradish peroxidase (HRP) chemiluminescence for quantification of α-fetoprotein (AFP) in serum from patients with hepatocellular carcinoma (HCC). Methods: A protein microarray assay for AFP was developed. Serum was collected from patients with HCC and healthy control subjects. AFP was quantified using protein microarray and enzyme-linked immunosorbent assay (ELISA). Results: Serum AFP concentrations determined via protein microarray were positively correlated ( r  = 0.973) with those determined via ELISA in patients with HCC ( n  = 60) and healthy control subjects ( n  = 30). Protein microarray showed 80% sensitivity and 100% specificity for HCC diagnosis. ELISA had 83.3% sensitivity and 100% specificity. Protein microarray effectively distinguished between patients with HCC and healthy control subjects (area under ROC curve 0.974; 95% CI 0.000, 1.000). Conclusion: Protein microarray is a rapid, simple and low-cost alternative to ELISA for detecting AFP in human serum.